TINDAK PIDANA PENDAFTARAN SERTIFIKAT HAK MILIK NO 70/SIDOMULYO MENGGUNAKAN ALAS HAK/DASAR PALSU NO. 168/3/MT/1979 OLEH BADAN PERTANAHAN NASIONAL (Studi Putusan Nomor : 646/PID/2013/PT.Mdn). - Jhon Tyson Pelawi; Syafrudin Kallo; Muhammad Hamdan; Suhaidi Suhaidi (Universitas Sumatera Utara, 2015)
ABSTRACT Some factors which cause criminal act in falsifying land certificates are as follows: the implementation of incorrect law, non-transparent legal enforcement, frail administrative system, the ignorance of the personnel of the National Land Board, people’s lack of knowledge in law, judges’ negligence in the hearing facts and evidence, the involvement of the military personnel in falsifying the certificates, and sanction stipulated in UUPA (Agrarian Law) is too lenient. Government Regulation No. 24/1997 on Land Registration and Article 52 of UUPA on criminal sanction state that perpetrators in land crime, as it is regulated in Article 19 of UUPA, is sentenced to 3 months and fined Rp 10.000, Law Enforcement for perpetrators who have falsified land certificates is regulated in Articles 263 to 266 of the penal code on criminal act of falsifying certificates and Articel 52 of UUPA on criminal sanction on Land Crime. in order to forestall, handle, and settle the conflict on land, old feudalistic, centralistic bureaucratic, authoritative, and repressive paradigm should be changed to populist, democratic, and decentralized paradigm and respect for human rights. Keywords: Criminal Act, Registering Debenture, Based on Legal Basis